Small and medium enterprises in the context of regional development and innovations - Gulnara Ruchkina; Marina Melnichuk; Svetlana Frumina; Grzegorz Mentel (Journal of International Studies)
The current state of economic development and innovations’ support often brings small and medium enterprises (SMEs) at the forefront of government fiscal policy. Various policy measures targeted at SMEs’ support and development necessarily include measures on promotion of innovations within small business. However, despite substantial efforts undertaken by the authorities to increased financial injections into this area, development of innovations by small businesses faces many obstacles. Statistics on the registered small and medium enterprises shows that the sharp rise of entrepreneurship observed in the early 1990s changed for the stagnation towards the end of the decade and sluggish dynamics of the present time. Unfortunately, as practice shows, measures taken so far do not stimulate significant changes in the development of small business. Moreover, differentiation of small businesses between regions is only increasing, as it is manifested through substitution of divergence for convergence. Our paper analyzes the legal framework regulating small business development as well as state of innovations within SMEs so that to identify the main indicators contributing to sustainable regional economic growth.